Avaliação de alunos do atendimento educacional especializado de uma escola pública de Belém através da school function assessment/avaliação da função escolar (SFA) - ARTNER, Carlos Alberto (2023)
With the evolution of Inclusive Education (IE) in Brazil, were introduced policies governing the access of all to education, without any exception. From this comprehensive perspective, the Occupational Therapy (OT) is inserted in this field in order to contribute to the process of inclusion with school staff through the healtheducation interface. To act in this area, is essential on the occupational therapy process an initial assessment that collects data on the student and the aspects that make up the school environment. To this end, various evaluation protocols can be used. This research aimed to evaluate students of the Specialized Educational Service (SES) through the School Function Assessment (SFA). The protocol consists of three parts which assess respectively: participation in school environments, Task Supports and performance in school activities. It was adopted in this study the type of quantitativedescriptive crosssectional survey. The research subjects were the SES teachers of the Elementary School Padre Leandro Pinheiro (BelémPA) that evaluated 8 students who met the inclusion criteria of the sample. The results of the first part pointed the transport category with the lowest score. Concerning the second part, there was little use of adaptations. In the last part was no difference in the performance of physical tasks compared to cognitive / behavioral, as explained by the diagnosis of the students in the sample. From the application of the SFA, it was possible to view t he student holistically, as a protocol that enables a holistic view of the student. Because of the diagnosis of the evaluated students, the changes and difficulties in cognitive / behavioral aspects directly affect school participation of the sample. The study also revealed a possibility of action of OT, as well as its benefits.